2019
DOI: 10.3390/nu11051119
|View full text |Cite
|
Sign up to set email alerts
|

Are Older Adults without a Healthy Diet Less Physically Active and More Sedentary?

Abstract: Few studies on older populations consider several energy balance-related behaviors together. This cross-sectional study compared subjectively and objectively measured physical activity (PA) and sedentary behavior (SB) patterns between older adults with and without a healthy diet. We recruited 127 community-dwelling older Taiwanese adults (69.9 ± 5.0 years); data were collected during April and September 2018. Objectively measured total PA, moderate-to-vigorous PA, light PA, step count, total sedentary time, du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…This result was consistent with a previous study in which as total LTPA increased, the adherence to MD did too [49]. Furthermore, it was found that older adults with unhealthy diet tended to engage in more inactive lifestyle than older adults with a healthy diet [50].…”
Section: Discussionsupporting
confidence: 92%
“…This result was consistent with a previous study in which as total LTPA increased, the adherence to MD did too [49]. Furthermore, it was found that older adults with unhealthy diet tended to engage in more inactive lifestyle than older adults with a healthy diet [50].…”
Section: Discussionsupporting
confidence: 92%
“…Evidence based on the medical Qigong and Tai-chi also shows that cognitive function improvement is related to the Chi-Kung practice, including hand-shaking moments 73 , 74 . PA with low intensity and resistance yielded less health-promoting effects; most elderly individuals were engaged in a more specific PA in parks or schools near their homes, and the intensity of PA was insufficient 75 , 76 . Nutrient supplements with fruits and vegetables are needed to reduce the risk of cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…The recruitment was announced through local advertisements and notifications at health centers, and those interested in the study could contact the recruiters easily. Detailed information regarding the recruitment process has been presented elsewhere [20]. Physical performance, such as lower limb strength, was tested on-site by the interviewers.…”
Section: Participantsmentioning
confidence: 99%
“…The instruction "for example, three servings of vegetables and two servings of fruit every day" according to Taiwanese dietary guidelines [30] was provided along with the question. This question represented the dietary behavior of consuming a balanced selection of foods, which was used widely in previous studies in relation to older adults in Taiwan [20,31,32].…”
Section: Self-reported Selection Of Foodsmentioning
confidence: 99%